Determinants of capital structure : A comparative study in Malaysia and Indonesia - Hadi, Ahmed Hassan (2014)
The study investigates the determinants of the capital structure of 237 manufacturing firms listed in Malaysia and Indonesia stock exchange from 2005-2012. Ordinary least square and fixed effect model have been used to estimate the relationship between firmspecific determinants (firm size, profitability, tangibility, non-debt tax shields, liquidity and share price performance) and country-specific determinants (GDP growth, inflation and interest rate). The result suggests that firm-specific and country-specific determinant varies across Malaysia and Indonesia. The results show that firm size, tangibility, and non-debt tax shields are significantly and positively related to overall leverage and longterm leverage, while liquidity and share price performance are negatively related to leverage of Malaysian firms. For Indonesian firms, profitability, tangibility and non-debt tax shields are positively related to overall and long-term leverage, but firm size, liquidity and share price performance are negatively related to overall leverage and long-term leverage. Inflation is positively related to overall leverage under the fixed effect model, interest rate is negatively related to overall leverage, while GDP growth is negatively related with long-term leverage. The results also show that firm-specific factors play an important role in determining the capital structure before and after the 2008 financial crisis. The results of this study support the pecking order theory, the trade-off theory, market timing theory and the agency theory. The study has laid groundwork and detailed explanation about the determinants of capital structure in Malaysian and Indonesian manufacturing firms.